Everything you need to know about world history homework - Zeman, Anne, 1951-; Kelly, Kate. (New York : Scholastic Reference, 1997)
Provides fourth to sixth grade students and parents with information they need to complete world history assignments.
"A desk reference for students and parents.".
"In collaboration with UFT Dial-a-teacher"--Cover.
Includes index.
L.A. Recommended Foreign Language.
Library Talk.
6.6
Keywords: Homework -- Juvenile literature; World history -- Study and teaching. -- Juvenile literature; Homework; World history -- Study and teaching; Study skills; World history -- Study and teaching